IMPLEMENTASI VOICE OVER INTERNET PROTOCOL DAN ANALISIS QUALITY OF SERVICE PADA PT. SENIMBA BAY RESORT - Supardianto; Celine Dion (ABEC Indonesia, 2021)
Voice over Internet Protocol (VoIP) is internet-based communication technology. The use and maintenance of a VoIP system require low costs compared to Private Automatic Branch eXchange (PABX) technology. To produce a good and clear voice, VoIP requires stable internet. The working process of VoIP is to convert analog signals into digital signals. Testing feasibility of a VoIP system, it is necessary to analyze the Quality of Service (QoS). The QoS parameters tested are delay, jitter, packet loss, and throughput. The VoIP implementation process and QoS analysis were carried out at PT. Senimba Bay Resort aims to build a communication system that is much more effective than before